SISTEM MONITORING SUHU DAN KELEMBABAN BERBASIS IoT PADA PROSES PEMBUATAN PUPUK ORGANIK PADAT - Muhammad Saiful Amin; Ambar Susanti; Primaadi Airlangga (SAINTEKBU, 2021)
The Process Of Making Organic Fertilizer requires a certain temperature and humidity to keep the microorganisms used to be able to stay alive and can decompose perfectly, for that it is necessary to monitor temperature and humidity. Along with the development of this technology, it can be done by remote automation using a microcontroller on the ESP8266 nodemcu based on IoT (Internet Of Things), which is combined with the DS18B20 sensor for temperature measurement and soil moisture sensor, as a humidity meter with a temperature unit of Â°C. The humidity meter is an analog signal, the larger the value, the more humid of organic fertilizer. Acquired measurement data is sent to the Smartphone using an internet-connected ESP8266 monitoring temperature and humidity, which can be viewed via the Blynk App.